In vitro antiplasmodial activity and cytotoxicity of ten plants used as traditional medicine in Malaysia. - Abdullah, Wan Omar; Unyah, Ngah Zasmy; Awang Hamat, Rukman; Omar, Baharudin; Abd Ghani, Mohd Kamel; Mohammad Rayani,; Hatam, Gholam Reza (Universiti Kebangsaan Malaysia Press, 2011)
Dichloromethane and methanolic extracts of each plant were tested for their antiplasmodial activity on chloroquineresistant strain of Plasmodium falciparum (FCB strain), based on lactate dehydrogenase activity. Cytotoxicity was assessed with the MTT test on MRC-5 human diploid embryonic lung cells. Most extracts of ten selected plants used in Malay traditional medicine in Malaysia had activity in vitro. This supports continued investigations of traditional medicine in the search for new antimalarial agent. The compounds responsible for the observed antiplasmodial effects are under investigation.